Integrating primary school notification system with SMS technology / Hawa Mohd Ekhsan, Jiwa Noris Hamid and Nurul Syakilah Mazlan - Mohd Ekhsan, Hawa; Hamid, Jiwa Noris; Mazlan, Nurul Syakilah (UiTM Cawangan Perlis, 2018)
This study presents the use of web SMS technology as an alternative method for primary school notification system. By integrating the system with SMS gateway, it will enable the primary school notification system to send information to parents' mobile phone directly. The traditional methods of notifying parents about the school matters by sending letter and written memo are time consuming and the updated information may not reach the parents. This integration allows information to be disseminated from computer to mobile phone at any time without requiring face to face meeting or the use of other media such as paper-based notice or verbal notice from the students. Furthermore, parents can always be alert and aware of the latest announcement or information no matter where they are. A usability testing was conducted to 20 users to survey the feedback on SMS technology to notify parents. The results from the testing stated that 100% of users give positive feedback about the ease of use and satisfied that the system can replace old systems. Based on the results, it shows that the integration of primary school notification system with SMS technology is highly recommended.